2007
DOI: 10.1101/gad.1536107
|View full text |Cite
|
Sign up to set email alerts
|

U2 toggles iteratively between the stem IIa and stem IIc conformations to promote pre-mRNA splicing

Abstract: To ligate exons in pre-messenger RNA (pre-mRNA) splicing, the spliceosome must reposition the substrate after cleaving the 5 splice site. Because spliceosomal small nuclear RNAs (snRNAs) bind the substrate, snRNA structures may rearrange to reposition the substrate. However, such rearrangements have remained undefined. Although U2 stem IIc inhibits binding of U2 snRNP to pre-mRNA during assembly, we found that weakening U2 stem IIc suppressed a mutation in prp16, a DExD/H box ATPase that promotes splicing afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 64 publications
(136 reference statements)
7
130
0
Order By: Relevance
“…Parts of the primary sequence and secondary structure of yeast U2 snRNA are shown. Two competing structures (Hilliker et al, 2007;Perriman and Ares, 2007), stem-loop IIa (top) and stem IIc (bottom), are schematically represented. The base-pairing interactions between the U2 branch site recognition region and the pre-mRNA branch site are also schematically shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parts of the primary sequence and secondary structure of yeast U2 snRNA are shown. Two competing structures (Hilliker et al, 2007;Perriman and Ares, 2007), stem-loop IIa (top) and stem IIc (bottom), are schematically represented. The base-pairing interactions between the U2 branch site recognition region and the pre-mRNA branch site are also schematically shown.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, how do induced pseudouridines affect premRNA splicing? Recently, the Ares and Staley labs proposed a model reliant on the fact that U2 toggles between two mutually exclusive structures, stem-loop IIa and stem IIc, during splicing (Hilliker et al, 2007;Perriman and Ares, 2007) (Fig. 7).…”
Section: Pseudouridine Differs From Its Counterpart Uridine In Severalmentioning
confidence: 99%
“…Finally, Prp22p, which promotes release of the mRNA after exon ligation (15,16), discriminates against mutated consensus sites before exon ligation (11). Fidelity is also promoted by the sequestration of suboptimal substrates through equilibration between distinct spliceosomal states (17)(18)(19).…”
mentioning
confidence: 99%
“…13,24,65 Using protein-free snRNAs, Yuan and colleagues 29 used a FRETbased assay that took advantage of the increase in the luminescence other in the folded, active structure of the U6/U2 complex found in the activated spliceosomes, perhaps in an arrangement similar to the one found in group II introns. 12,14 While several studies indicate that the transition from the first step of splicing to the second involves a conformational change, 54,[57][58][59] it is likely that the same three domains of U6 are involved in catalysis of both steps of splicing. Mutagenesis studies have suggested a critical role for all three regions in both the first and second steps of splicing.…”
Section: The Three Dimensional Positioning Of Snrnas In the Active Sitementioning
confidence: 99%
“…While the active site elements undergo a minor remodeling between the two steps of splicing, several other RNA-RNA interactions including snRNA-substrate interactions seem to be significantly rearranged during the catalytic cycle of the spliceosome. [57][58][59][60][61] …”
Section: The Three Dimensional Positioning Of Snrnas In the Active Sitementioning
confidence: 99%